The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1080/19386362.2017.1311086
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of clayey soil relevant for clogging potential

Abstract: Due to its advantages, including reduced operation time and cost, tunneling with boring machines in urban areas has become a popular technique over handtunneling or open-trench excavations. However, tunneling in clayey soil poses a great challenge since the mechanical and physical properties of clays cause different issues, one of which is clogging. To solve this problem, engineers have treated the soils with different soil conditioners in order to change their rheological properties, improve their manageabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In this situation, the excavation operation should be stopped, and the cutting tools on the cutter head should be cleaned, and then the excavation operation should be resumed. This causes an increase in the excavation time, an increase in costs, and a decrease in excavation efficiency (Hernandez et al, 2018). The clogging occurs due to the adhesion between the soil and the cutter head and conveyor belt in EPB excavation machines.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, the excavation operation should be stopped, and the cutting tools on the cutter head should be cleaned, and then the excavation operation should be resumed. This causes an increase in the excavation time, an increase in costs, and a decrease in excavation efficiency (Hernandez et al, 2018). The clogging occurs due to the adhesion between the soil and the cutter head and conveyor belt in EPB excavation machines.…”
Section: Introductionmentioning
confidence: 99%
“…The shear strength of the soil can then be calculated based on the measured torque and the dimensions of the vane [19]. Hernandez et al [20] used a fully automatic laboratory miniature vane shear device to measure the undrained shear strength of clay in different states. Zumsteg et al [21] used the MVST to measure the undrained shear strength of different mixtures of kaolinite conditioned by foam and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Burbaum and Sass (2017) [3] conducted experiments to analyze the influence of two elements, i.e., the pore water tension (suction) of the soil and the permeability of the soil, on the adhesion of cohesive soils to solid surfaces, and presented the results of adhesion tests and pore water tension measurements during the adhesion tests. [14] indicated that the initial water content, the roughness of shear plate, and the percentage of additives have a significant effect on clogging potential, and an empirical diagram to understand the clogging potential by relating the clogging potential to soil properties was also plotted. The occurrence of the cutting head clogging is closely related to the physical and mechanical properties of the soils in the cutting face.…”
Section: Introductionmentioning
confidence: 99%